2012
DOI: 10.1029/2011jc007099
|View full text |Cite
|
Sign up to set email alerts
|

Classification of remote Pacific coral reefs by physical oceanographic environment

Abstract: [1] The oceanographic environment is a key element in structuring coral reef ecosystems by setting the range of physical and chemical conditions in which coral reef-builders live. A cluster analysis of physical and chemical oceanographic data is used to classify coral habitats in the remote tropical and subtropical Pacific Ocean based on average temperature, temperature seasonal cycle, nutrient levels, salinity, aragonite saturation state, storm frequency, intense hurricane hits, and dissolved oxygen as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…PCA outputs (Fig. 6) and Pearson's correlations (Table 1) reveal associations between acoustic variables and observations from TLP, SPC and photoquadrat data that were consistent across the entire Hawaiian archipelago, and within the 2 oceanographic habitats considered (Freeman et al 2012).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…PCA outputs (Fig. 6) and Pearson's correlations (Table 1) reveal associations between acoustic variables and observations from TLP, SPC and photoquadrat data that were consistent across the entire Hawaiian archipelago, and within the 2 oceanographic habitats considered (Freeman et al 2012).…”
Section: Resultsmentioning
confidence: 75%
“…Grey lines and filled circles indicate mean acoustic pressure spectral density levels during the periods and within the bands indicated (k: kHz). Dark blue and cyan triangles indicate the position of field sites within the 'cool tropics' and 'high latitudes' oceanographic regimes, respectively (Freeman et al 2012). A general trend from 07:00 to 14:00 h is evident in the sites ranging from more algae-dominated to more coral-dominated, which is also reflected in the acoustic metrics with low-frequency sounds characterizing reefs with positive ecological indicators, and high-frequency sounds characterizing reefs with negative ecological indicators (Radford et al 2010) from ecosystem-wide trends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have been important for establishing environmental limits to coral reef development [3], identifying broad geographic patterns in environmental habitats in which coral reefs reside [13], [15], and assessing the susceptibility of coral reefs to anomalies in environmental forcings on a global scale [11], [12], [16]. In many previous studies, [3], [13], [14] environmental data were synthesized at 1 × 1° (12,100 km 2 ); a coarse resolution when compared to the size of many of the islands and atolls in the Pacific. Research has shown environmental conditions such as productivity [17], [18] and temperature [19], [20] proximate to islands can be distinct from regional conditions.…”
Section: Introductionmentioning
confidence: 99%